دور سلاسل الإمداد في تعزيز التنافسية ، دراسة حالة : الصادرات الجزائرية خارج قطاع المحروقات في الفترة الممتدة من 2007 إلى 2024 - خديجة خاوة; عائشة صالحي; ليلى زعبوب (جامعة الوادي University of Eloued, 2025)
تهدف الدراسة إلى بيان أثر سلاسل الإمداد و التوريد على التنافسية ، من خلال الأدبيات النظرية لكل منهما، و إيضاح العلاقة فيما بينهما . ثمّ التطرق إلى قياس العلاقة بين تنافسية الصادرات الجزائرية خارج قطاع المحروقات في الفترة 2007-2024 (مؤشر القدرة على التصدير) بدلالة مؤشرات الأداء اللوجستي (LPI) الفرعية (أداء الجمارك-سهولة ترتيب الشحنات-جودة الخدمات اللوجستية-البنية التحتية) ؛ حيث تم جمع البيانات الخاصة بمتغيرات الدراسة و تحليلها بالاعتماد على نموذج الانحدار الخطي المتعدد بطريقة المربعات الصغرى بواسطة البرنامج الإحصائيEVIEWS-12 .وتم التوصل إلى وجود أثر إيجابي متفاوت لهذه المؤشرات على الصادرات خارج قطاع المحروقات، فبالرغم من الإصلاحات اللوجستية في الآونة الأخيرة في مجال رقمة الإجراءات و تسهيل الشحن الدولي، لاتزال هناك تحديات هيكلية في مجال الجمارك و البنية التحتية تؤكد على تبني استراتيجيات شاملة و متكاملة لتطوير سلاسل الإمداد و التوريد . The study aims to demonstrate the impact of supply chains on competitiveness, through the theoretical literature of each, and to clarify the relationship between them. It then addresses measuring the relationship between the competitiveness of Algerian exports outside the hydrocarbons sector during the period 2007-2024 (export capability index) in terms of the sub-indices of logistics performance (LPI) (customs performance - ease of arranging shipments - quality of logistics services - infrastructure). Data for the study variables were collected and analyzed using a multiple linear regression model using the least squares method using the EVIEWS-12 statistical program. It was found that these indicators have a varying positive impact on exports outside the hydrocarbons sector. Despite recent logistical reforms in the field of digitizing procedures and facilitating international shipping, there are still structural challenges in the field of customs and infrastructure that emphasize the adoption of comprehensive and integrated strategies to develop supply chains.
ماستر العلوم التجارية
Keywords: سلاسل الإمداد; التوريد; التنافسية; تنافسية الصادرات; Supply chains; competitiveness; export competitiveness